Special education and services in Cagayan De Oro City development, problems and prospects - Aguilar, Judith V. Planas (College of Education, University of the Philippines Diliman, 2008)
This thesis is a historical-decriptive study aimed at determining the development of special education and related services in Cagayan de Oro City from the time it started to its present conditions. It also determined the congruence or disparity of SPED practices and services with the standards provided by the Department of Education as well as the Best Practices recommended by the respected authorities in the field. The objectives were achieved through 4 focus group discussions, 20 interviews, a site visit, and a survey involving 149 respondents from 12 schools. Parents reported that the lone SPED center in CDO needed to improve its services in order to comply with the policies set out by the government. Discrepancy was noted in the SPED and services particularly in the areas of school design, the teaching of life skills, and assessment. Partial congruence was seen in the school and educators' philosophy, accommodations, program and curriculum.